Microfluidic contact lenses - Jiang,N; Montelongo,Y; Butt,H; Yetisen,AK (Small, 2018)
Contact lens is a ubiquitous technology used for vision correction and cosmetics. Sensing in contact lenses has emerged as a potential platform for minimally invasive point-of-care diagnostics. Here, a microlithography method is developed to fabricate microconcavities and microchannels in a hydrogel-based contact lens via a combination of laser patterning and embedded templating. Optical microlithography parameters influencing the formation of microconcavities including ablation power (4.3 W) and beam speed (50 mm s−1) are optimized to control the microconcavity depth (100 µm) and diameter (1.5 mm). The fiber templating method allows the production of microchannels having a diameter range of 100–150 µm. Leak-proof microchannel and microconcavity connections in contact lenses are validated through flow testing of artificial tear containing fluorescent microbeads (Ø = 1–2 µm). The microconcavities of contact lenses are functionalized with multiplexed fluorophores (2 µL) to demonstrate optical excitation and emission capability within the visible spectrum. The fabricated microfluidic contact lenses may have applications in ophthalmic monitoring of metabolic disorders at point-of-care settings and controlled drug release for therapeutics.